Efektivitas Pelatihan Mindful Parenting Terhadap Penurunan Kecenderungan Child Maltreatment Pada Anak Usia Dini - Min Yatul Rahma; Arcivid Chorynia Ruby (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Child maltreatment is a risky act and it has a serious impact, especially for early childhood. Mindful parenting training is one of the parenting concepts that can minimize the occurrence of child maltreatment. This study aims to examine the effectiveness of mindful parenting training on reducing the tendency of child maltreatment in parents. This study uses a pre-experimental design method with a one group pre-test-post-test design. The sample selection was determined using purposive sampling technique. The subjects in this study amounted to 35 parents of students at Aisyah Integrated Birrul Walidain Kindergarten in Kudus, Central Java. Hypothesis testing was conducted using paired sample t-test, where a significance value of P = 0.000 (P < 0.05) was obtained, which means that the hypothesis is accepted. In other words, mindful parenting is effective in reducing the tendency of child maltreatment by parents in early childhood